An investigation of surface properties, local elastic modulus and interaction with simulated pulmonary surfactant of surface modified inhalable voriconazole dry powders using atomic force microscopy. Issue 31 (9th March 2016) - Arora, Sumit; Kappl, Michael; Haghi, Mehra; Young, Paul M.; Traini, Daniela; Jain, Sanyog
Abstract : l -Leucine modified voriconazole spray dried micropartcles. Abstract : l -Leucine is used as the most common force control agent used in the inhaled dry powder formulations. In this study, the effect ofl -leucine on the surface morphology, surface energy and the Young's modulus of the composite spray dried particles was studied. In addition, howl -leucine modifies the interaction of particles with a simulated pulmonary surfactant is also studied. Voriconazole (VRZ) was spray dried with different concentrations ofl -leucine from hydroalcoholic solutions. Formulations were found to possess irregular morphology. Surface concentration ofl -leucine was increased with increasing feed concentration and plateaued at about 20% w/wl -leucine. Atomic force microscopy (AFM) coupled with drug colloid probe enabled measurement of cohesion forces between the prepared formulations and found cohesion to be reduced significantly ( p < 0.05) with the increase ofl -leucine concentration. Peak Force Tapping enabled characterization of nanomechanical properties (elasticity and deformation) of formulations. Co-spray dryingl -leucine with VRZ does not seem to have any influence on the Young's modulus of the formulations. Lastly, AFM revealed that the surface chemistry of the drug particle and pulmonary surfactant, as well as the contact geometry of the interacting surfaces, plays an important role in determining nature and extent of interaction between inhaled drug particles and pulmonary surfactant.